2013
DOI: 10.1183/09059180.00005613
|View full text |Cite
|
Sign up to set email alerts
|

How to adapt the pulmonary rehabilitation programme to patients with chronic respiratory disease other than COPD

Abstract: Dyspnoea, fatigue, reduced exercise tolerance, peripheral muscle dysfunction and mood disorders are common features of many chronic respiratory disorders. Pulmonary rehabilitation successfully treats these manifestations in chronic obstructive pulmonary disease (COPD) and emerging evidence suggests that these benefits could be extended to other chronic respiratory conditions, although adaptations to the standard programme format may be required. Whilst the benefits of exercise training are well established in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 115 publications
(148 reference statements)
1
81
0
11
Order By: Relevance
“…[27][28][29] Marcisz et al 30 showed that FVC, forced expiratory volume in one second, VC, MVV, maximum midexpiratory flow rate 25-75%, and peak expiratory flow rate values were significantly decreased in SSc patients compared to controls. Pulmonary function test results of our patients are similar to this study.…”
Section: Resultsmentioning
confidence: 99%
“…[27][28][29] Marcisz et al 30 showed that FVC, forced expiratory volume in one second, VC, MVV, maximum midexpiratory flow rate 25-75%, and peak expiratory flow rate values were significantly decreased in SSc patients compared to controls. Pulmonary function test results of our patients are similar to this study.…”
Section: Resultsmentioning
confidence: 99%
“…Although physical training interventions described for ILD show great similarities with interventions used in other chronic lung diseases, e.g. COPD [2,75], lessons learned from other disorders, like neurological and rheumatologic disorders, should be taken into account as well [6]. Studies carried out so far involving subjects with sarcoidosis have shown that physical activity can reduce their symptoms.…”
Section: Optimizing Physical Therapymentioning
confidence: 99%
“…The intensity of the training should be personalized, tailored to the individual -which might also include adjustments for daily fluctuations in energy levels -to avoid aggravating the impairments, which would result in high dropout rates [2]. Besides, as with other chronic cardiopulmonary diseases, exercise limitation in sarcoidosis is most likely to be multifactorial, meaning that exercise capacity is not limited by any single component of the disease process, but rather by their collective quantitative interaction(s).…”
Section: Expert Commentarymentioning
confidence: 99%
See 2 more Smart Citations